Gradient of vaccine hesitancy among French men having sex with men: An electronic cross-sectional survey in 2022 - Emeline Brosset; Lisa Fressard; Chloé Cogordan; Aurélie Bocquier; Margot Annequin; Michel Bourrelly; Jean Constance; David Michels; Marion Mora; Stéphane Morel; Camilla Oliveri; Gwenaëlle Maradan; et al. (Taylor & Francis Group, 2023)
ABSTRACTIn developed countries, vaccinations against hepatitis B (HBV), hepatitis A (HAV), and human papillomavirus (HPV) are often recommended to men who have sex with men (MSM) because of the risky sexual practices in which some engage. Vaccine coverage against these diseases is not optimal in France, probably due in part to vaccine hesitancy (VH). The overall aim of this survey among MSM was to estimate the prevalence of different grades of VH for these vaccines as well as of general VH (toward any vaccine). The specific objectives were to study the sociodemographic correlates of MSM specific and general VH and its association with vaccine uptake. A cross-sectional electronic survey (February-August 2022) collected information from 3,730 French MSM about their perceptions of HBV, HAV, and HPV and their related vaccines, to construct "specific VH" variables. Information about their past vaccination behaviors for any vaccine was used to construct a "general VH" variable, based on the World Health Organization definition. Almost 90% of MSM showed moderate or high specific VH for HBV, HAV, and/or HPV, and 54% general VH. A higher education level and comfortable financial situation were associated with lower grades of specific and general VH. Younger age was associated with less frequent specific VH and more frequent general VH. Specific VH, versus general, was more strongly associated with frequent self-reported non-vaccination against these three disease. Addressing their concerns about vaccines, improving their knowledge of vaccine-preventable sexually transmitted infections, and motivating them to get vaccinated are public health priorities.